2015
DOI: 10.1016/j.jphotochem.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A general kinetic model for the photothermal oxidation of polypropylene

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. A B S T R A C TA general kinetic model for the photothermal oxidation of polypropylene has been derived from the basic auto-oxidation mechanistic scheme in which the main sources of radicals are the thermolysis and photolysis of the most unstable species, i.e hydroperoxides. Thermolysis is a uni-or bi-molecular reaction whose rate constant obeys an Arrhenius l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…As peroxide products can themselves Andrady et al (1998) dissociate readily into radicals, the reaction sequence is autocatalytic. The main reactions involved in the sequence are as follows (François-Heude et al 2015 From a practical standpoint, it is the chain scission that accompanies this cyclic reaction sequence, which is of greater interest. The chain scission event is believed to be associated with one of the propagation reactions and is responsible for the loss in mechanical properties of the plastic material after exposure.…”
Section: Mechanisms Of Photo-oxidationmentioning
confidence: 99%
“…As peroxide products can themselves Andrady et al (1998) dissociate readily into radicals, the reaction sequence is autocatalytic. The main reactions involved in the sequence are as follows (François-Heude et al 2015 From a practical standpoint, it is the chain scission that accompanies this cyclic reaction sequence, which is of greater interest. The chain scission event is believed to be associated with one of the propagation reactions and is responsible for the loss in mechanical properties of the plastic material after exposure.…”
Section: Mechanisms Of Photo-oxidationmentioning
confidence: 99%
“…A mathematical expression for the oxidation rate was obtained through the conventional concepts of chemical kinetics by making four simplifying assumptions: (1) unicity of reactive site, i.e., oxidation occurs exclusively on the most labile CH bond; (2) low conversion ratios of oxidation process, i.e., concentration of reactive sites remains virtually constant; (3) constancy of initiation rate in the case of oxidation induced by an extrinsic factor; (4) steady-state for radicals concentrations in all oxidation cases, but also for hydroperoxides concentration in the case of pure thermal oxidation [66]. Cunliffe and Davis [67], Furneaux et al [68], and Audouin et al [69] developed kinetics model with the aim of describing other oxidation regimes of lower oxygen concentration than oxygen excess.…”
Section: Kinetics Of Photochemical Oxidation Of Polyolefinsmentioning
confidence: 99%
“…37 Thermolysis is a uni-or bi-molecular reaction whose rate constant obeys an Arrhenius law. 38 In contrast, photolysis is exclusively a unimolecular reaction and its rate constant is independent of temperature. 38 Using these premisses kinetic model of photothermal oxidation of polypropylene was developed.…”
Section: Pollutantsmentioning
confidence: 99%
“…38 In contrast, photolysis is exclusively a unimolecular reaction and its rate constant is independent of temperature. 38 Using these premisses kinetic model of photothermal oxidation of polypropylene was developed. 38 It was found that the model was only valid up to energy of 10 suns, most likely because of multiphotonic excitations or chromophores photosensitization.…”
Section: Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation